Incidentally detected pituitary macroadenoma in a case of neurofibromatosis type 1: A case report and review of literature (Indian Journal of Case Reports, 2021)
Neurofibromatosis is a cancer predisposition syndrome that leads to an increased risk of certain neural tumors. Neurofibromatosis type 1 (NF-1) presents with multiple neurofibromas which may be dermal or plexiform. Neurofibromatosis type 2 is characterized by bilateral vestibular schwannomas. Pituitary masses have been infrequently described in cases of NF-1. We describe the case of an incidentally discovered pituitary macroadenoma in a patient with NF-1. Apart from the macroadenoma, the patient had plexiform neurofibromas of the orbit, Lisch nodules of the iris, and café-au-lait spots. The patient was called for medical management but failed to show due to the COVID-19 pandemic.